Ultrasound diaphragmatic manual and semi-automated motion measurements: Application in simulated and in vivo data of critically ill subjects - Loizou, Christos P.; Chrysostomou, Constantinos; Minas, Giorgos; Pattichis, Constantinos S. (Computer methods and programs in biomedicine, 2020)
•Diaphragmatic muscle motion characteristics may provide useful information about diaphragmatic function.•Diaphragmatic motion semi-automated and manual measurements are not statistically significantly different.•The diaphragmatic excursion derived in this study for the subjects investigated at risk or had presumed diaphragmatic weakness was significantly lower than that of normal subjects based on published literature.•Diaphragmatic ultrasound video recorded in the course of a B-mode examination can be used to generate an M-mode image where diaphragmatic motion measurements can be performed.•The usefulness of the proposed system still remains to be evaluated in the clinical practice in the assessment and follow up of patients with diaphragmatic weakness or paralysis. Ultrasound diaphragmatic muscle motion characteristics may provide useful information about normal or abnormal diaphragmatic function and indicate diaphragmatic weakness, or paralysis. In the present work we propose and evaluate an integrated semi-automated analysis system for the quantitative analysis of ultrasonic motion from ultrasound diaphragmatic videos. The proposed system was evaluated in simulated videos and in 13 patients, four of whom patients were mechanically ventilated. The major steps of the methodology were as follows: video normalization, despeckle filtering, generation of an M-Mode image, snakes segmentation, and motion measurements. The following manual (-/) vs semi-automated (/-), (median±IQR) measurements, which are routinely carried out by the experts, for assessing the severity of the disease, were computed. For the simulated videos the diaphragmatic excursion was 1.80±0.00 cm / 1.76±0.03 cm. For all the real ultrasound videos investigated in this study the following measurements were computed: (i) diaphragmatic excursion: 0.84±0.15 cm / 0.83±0.14 cm, (ii) inspiration time (Tinsp): 0.71±0.18 sec / 0.70±0.15 sec, (iii) total breathing time for one cycle (Ttot): 1.71±0.37 sec / 1.67±0.37 sec, (iv) diaphragmatic curve slope: 1.29±0.36 cm/sec / 1.27±0.36 cm/sec, and (v) relaxation rate (RR): 0.82±0.17 cm/sec / 0.82±0.18 cm/sec. Manual and semi-automated measurements were very close with non-statistical significant differences and strong correlations between them. It is anticipated that the proposed system might be useful in the clinical practice in the assessment and follow up of patients with diaphragmatic weakness or paralysis and aid in the separation of normal and abnormal diaphragmatic motion. Further validation and additional experimentation in a larger sample of videos and different patient groups is required.